Nuclear study of the exotic neutrino interactions - Papoulias, D. K.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
Open neutrino physics issues require precision studies, both theoretical and experimental ones, and towards this aim coherent neutral current neutrino-nucleus scattering events are expected to be observed soon. In this work, we explore ν -nucleus processes from a nuclear theory point of view and obtain results with high confidence level based on accurate nuclear structure cross sections calculations. The present study explores the differential event rates as well as the total number of events expected to be measured by nuclear detectors, indicating measurable rates. We concentrate on the possibility of detecting supernova neutrinos by using massive detectors like those of the GERDA and SuperCDMS dark matter experiments and at spallation neutron source facilities (at Oak Ridge National Lab) by the COHERENT experiment.